2014
DOI: 10.4236/ijg.2014.53025
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effects of Atmospheric Pressure in the Time Series of Muon Detector Using the Method of Spectral Analysis

Abstract: This paper presented a study of the effects of atmospheric pressure in the time series of muon detector using the method of spectral analysis of iterative regression. In which it observed that the periods of 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Many works have analyzed the pressure and temperature effects on the observed muon intensity through different methods (Ambrosio et al, ; Yanchukovsky et al, ; Adamson et al, ; Berkova et al, ; Dmitrieva et al, ; Tolkacheva et al, ; Braga et al, ; de Mendonça et al, ; Rigozo, ; Zazyan et al, 2015; Mendonça et al, 2016; An et al, ; Maghrabi & Almutairi, ). By comparing several different methods, de Mendonça, Braga, Echer, Dal Lago, et al, found that the mass‐weighted method is the best for removing the temperature effect from the data recorded in the vertical channel of surface muon detectors.…”
Section: Introductionmentioning
confidence: 99%
“…Many works have analyzed the pressure and temperature effects on the observed muon intensity through different methods (Ambrosio et al, ; Yanchukovsky et al, ; Adamson et al, ; Berkova et al, ; Dmitrieva et al, ; Tolkacheva et al, ; Braga et al, ; de Mendonça et al, ; Rigozo, ; Zazyan et al, 2015; Mendonça et al, 2016; An et al, ; Maghrabi & Almutairi, ). By comparing several different methods, de Mendonça, Braga, Echer, Dal Lago, et al, found that the mass‐weighted method is the best for removing the temperature effect from the data recorded in the vertical channel of surface muon detectors.…”
Section: Introductionmentioning
confidence: 99%